2015
DOI: 10.1111/jdi.12382
|View full text |Cite
|
Sign up to set email alerts
|

Association of salivary alpha 2‐macroglobulin levels and clinical characteristics in type 2 diabetes

Abstract: Aims/IntroductionStudies suggest that salivary proteins can be used as potential non‐invasive markers for clinical diagnosis and screening for diabetes. Previous reports showed that plasma alpha 2‐macroglobulin (A2MG) levels were higher in diabetic patients, especially with diabetic complications. We investigated the relationship between salivary A2MG values and clinical characteristics in patients with type 2 diabetes.Materials and MethodsA total of 91 adults were recruited from our outpatient clinics. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 25 publications
4
17
1
1
Order By: Relevance
“…These results indicate that A2MG can be used as a diagnostic method for diabetes with high specificity. Our results are in line with other studies, which detected higher concentrations of A2MG in blood and saliva of prediabetic state subjects compared to healthy controls;[11121314] however, we have taken only DM2 patients, who already on treatment.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results indicate that A2MG can be used as a diagnostic method for diabetes with high specificity. Our results are in line with other studies, which detected higher concentrations of A2MG in blood and saliva of prediabetic state subjects compared to healthy controls;[11121314] however, we have taken only DM2 patients, who already on treatment.…”
Section: Discussionsupporting
confidence: 92%
“…In nephropathy, the biomarkers as serum creatinine are known to be raised, correlating with severity of kidney damage. Studies have indicated that A2MG is elevated in the blood of patients with type 1 and DM2, particularly in those with other complications due to diabetes, such as chronic renal failure or nephrotic syndrome,[1112] though in our study we have excluded stages IV–V patients of CKD. Serum creatinine, fasting plasma glucose, and postprandial plasma glucose are biomarkers of diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…We also found significantly high serum levels of α 2 -macroglobulin in DM patients compared with healthy volunteers. Several studies have reported a positive correlation between the HbA 1c level and α 2 -macroglobulin level in serum 2022 , but we did not. To negate the possibility that blood glucose levels in DM affect serum concentrations of α 2 -macroglobulin, we obtained the exact glycemic profiles of 57 individuals through 48-h CGM.…”
Section: Discussioncontrasting
confidence: 90%
“…Inter-assay and intra-assay CVs were small, and the results were stably reproducible. α 2 -macroglobulin levels in human serum have ranged by six orders of magnitude, and reported to be 0.5–2.5 µg/dL when measured using commercial ELISA kits 22,23,25 . Albumin and Ig molecules make up the greatest proportion of plasma proteins, but α 2 -macroglobulin is regarded to be one of top-12 abundant proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation